Integral equations of the theory of liquid in the study of hydration of macromolecules - Tikhonov, D A; Polozov, R V; Gorelov, A V; Timoshenko, E G; Kuznetsov, Iu A; Panchenko, L A; Dawson, K A (Biofizika, 1997)
An efficient numerical algorithm for solving integral equations of the theory of liquid in the RISM approximation for infinitely diluted solution of macromolecules with a large number of atoms is proposed. The algorithm is based on applying the non-stationary interactive methods for solving systems of linear algebraic equations. Using this technique we have calculated the solvent-solute atom-atom correlation functions for short fragment of DNA duplex of varying length in aqueous solution.